Policing the Stones: Music and Violence in Berlin. The Transnational Debates of the 1960s. - Bodo Mrozek (Criminocorpus)
This article analyses the violence that broke out at a 1965 Rolling Stones concert in West Berlin. In a close reading of records from the Berlin Police archives, it understands the events at the concert as the combined result of a lack of experience with new cultural forms of expression, old-fashioned ideas of ‘order’ deeply rooted in German history, and logistical failures. Analysing the aftermath of the concert, the article demonstrates how not only the event itself, but also the effects of rock music in general and the state of post-war youth, were discussed extensively in the media and even in a political debate at the Berlin city parliament. As a result, police reforms and new safety standards for concert halls and arenas were developed and internationally debated. Therefore, the article suggests considering the mid-sixties as a watershed (‘Schwellenzeit’) in the process establishing a new rock and pop culture.